STUDI PARTISIPASI MASYARAKAT TERHADAP PELAKSANAAN PROGRAM PNPM MANDIRI DI SUMATERA BARAT - Ermayanti Ermayanti; Hendrawati Hendrawati; Lucky Zamzami (Universitas Andalas, 2018)
This research article was conducted in the village of Sungai Beringin, Payakumbuh District, 50 Kota Regency. This regency is one of the best in West Sumatra, in the implementation of PNPM-MPd, especially in the village of Sungai Beringin. Achievements were obtained from this village is the improvement of the capacity of the community in physical and economic developing, women activities and helped the community to access the entire potential in the village of Sungai Beringin for realizing independent and prosperity of the community. This research used a qualitative approach, as a case of study with research focused to community participation into PNPM MPd levels, which these phenomena specifically attention about time, place and condition has happened in the village of Sungai Beringin. A result of the research shows that factors which influenced community participation can say still low. Planning of development participation is consistent and seriously from another side in PNPM MPd implementation, which consists of training of community empowerment, especially poverty community, internal factors which influenced are age, status, gender, jobs, and education. External factors also influenced all of the form and community participation level in meeting and discussion active in the meeting.